(untitled) (Education in the 21st Century, 2023)
The acceleration of digitization of almost all areas of the labor market creates a new demand for integrated specializations. The digital teacher-anthropologist specialization is an integrated specialization formed as a result of the intersection of four pedagogical faculties: pedagogical anthropology, digital pedagogy, pedagogical design, and social pedagogy. The labor market creates a new demand for professional specialists-digital pedagogues-anthropologists, who must ensure the computer socialization of the so-called "digital generation" in the digital environment. The seemingly very simple process at the theoretical and practical level has a radical, methodological sound, concerning significant changes in anthropological programs. The object of research in digital pedagogical anthropology is man + technology (Russian hybrid model) or man+artificial environment (American hybrid model), and the subject is computer socialization. Digitization of the labor market creates a new demand for integrated specialization-digital teachers-anthropologists, but so far universities do not meet the supply. The importance of the problem is also emphasized by the fact that the process of computer socialization in the digital environment is in progress, but there are no specialists who will ensure the quality and efficiency of this process during the training of the digital generation. Since the digital generation has features in the process of computer socialization, ignoring them will lead to the already existing fact of transformation of the levels of development into the three-hundred-year-old dialectic of man. A partial lack of coordination and direction is already noticeable, which, in turn, led to qualitative changes in the value system during socialization. The digital generation is not confident in its future, and faith in the future has weakened. The unpredictability and uncertainty of the future led to the choice of a new slogan: "today, at the moment, now"։ In the course of the conducted research, it becomes clear that in society there is a predestination of the problem and the formation of a working version. These are the first two important stages of creating demand for marketing. We believe that they will be followed by other stages of demand formation in the labor market, which will make it possible to predict the risks caused by the problem and the primary demand will turn into a double demand. The primary demand is for the newly emerging specialization in the labor market, and the dual demand is the propensity to specialize. We suggest that if the market will have a double demand, then in the master’s program to give specialization, including or training social educators appropriate courses of digital teacher-anthropologist, since the program content of the bachelor’s degree corresponds, but adding courses: digital pedagogy, pedagogical design, digital pedagogy.